The Concept of Life and Death: A Comparative Analysis of Darwinism, Christianity, Hinduism, and Islam from the Perspective of Islamic Creed (Aqidah) - Haswira Salleh Ahim (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2026)
Discussions regarding the concepts of life and death in the modern era are increasingly influenced by scientific and secular approaches which tend to deny the spiritual dimension, as well as giving rise to errors in understanding the meaning of human existence. Although various traditions such as Darwinism, Christianity and Hinduism offer their own interpretations, there is a significant gap in understanding, especially from the perspective of Islamic faith. In this regard, this study aims to analyze the concepts of life and death based on the perspectives of Darwinism, Christianity, Hinduism and Islam and assess the differences from the perspective of Islamic beliefs to determine the most comprehensive approach in understanding the meaning of human existence. This study uses a qualitative approach based on library analysis by examining primary sources such as the Al-Qur'an and hadith and secondary sources from related academic works and journal articles. Data were analyzed using thematic content analysis methods and critical comparison methods to identify similarities and differences between each perspective. The results of the study show that Darwinism provides an explanation that is limited to biological aspects without the dimension of life's purpose, while Christianity and Hinduism maintain spiritual elements but have certain theological and eschatological issues. In contrast, Islam offers a more holistic and balanced approach by combining the dimensions of the world and the afterlife, and emphasizes the concepts of monotheism, individual responsibility and life after death as the main principles in understanding the meaning of human existence.